Improving Citrus Peel Essential Oil Production Using Aspergillus Niger as A Biological Pretreatment - Aldro Alfaridzi, Berly; Diana; Cahyari, Khamdan (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Orange peel represents a promising renewable feedstock for essential oil production; however, the rigid lignocellulosic matrix restricts the efficiency of conventional extraction techniques. This study investigates the effectiveness of biological pretreatment in enhancing essential oil yield from orange peel through fungal fermentation. Pretreatment was conducted using Aspergillus niger to modify the lignocellulosic structure, followed by essential oil extraction and statistical evaluation of process parameters. The results demonstrate that biological pretreatment significantly increases essential oil yield compared with untreated samples. Optimal conditions were achieved at an inoculum concentration of 2.5%, glucose supplementation of 2.5 g, and a fermentation duration of 2 days. The improved extraction performance is attributed to enzymatic degradation of structural components, which enhances oil release. These findings highlight the potential of A. niger – based biological pretreatment as an efficient and environmentally sustainable strategy for valorizing orange peel waste in essential oil production.